Пишу себя, иду к себе...: стихотворения / Валентина Горизонтова - Горизонтова Валентина (Успех], 2008)
Экземпляры: аб. (20190719) / Инвентарный номер: 59711 / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: Г 69 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5